Implementasi Pelaksanaan Program I-HELP (Integrated Help Promoting School) pada Sekolah Menengah Pertama di Jakarta - Arroyyan, Rachma Dhiyaa'; Handayani, Sarah (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background. The I-HELP (Integrated Help Promoting School Programs) initiative is a school-based behavioural change intervention that integrates health values and belief-related variables into daily school activities. This program was developed as a follow-up to the collaboration between Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA) and SEAMEO RECFON. Aim. his study aims to describe implementation of the I-HELP (Integrated Help Promoting School Programs) at the junior high school level in Jakarta in 2022. Method. This qualitative research employed a case study design conducted at SMP Muhammadiyah 4 and SMP Muhammadiyah 36 Jakarta. Data collection techniques included in-depth interviews, focus group discussions (FGDs), and a review of documents related to the implementation of the I-HELP Program. Data were analyzed using thematic analysis and content analysis to evaluate the process of program implementation. To strengthen the validity of the findings, methodological triangulation was applied through interviews with school principals, health promotion officers, teachers, and members of the I-HELP team from SEAMEO RECFON. Additionally, observations of school conditions and program activities, as well as an examination of relevant documents, were conducted. Result. The findings indicate that both schools implemented the I-HELP Program in alignment with global indicators for health-promoting schools. Furthermore, each school optimized its available resources to support program execution.